2019
DOI: 10.18689/ijeg-1000107
|View full text |Cite
|
Sign up to set email alerts
|

Does Application of Brassinosteroids mitigate the Temperature Stress in Plants?

Abstract: The temperature across the globe is constantly changing for the worse of the biotic beings viz., the flora and fauna. Rapid temperature changes are the result of continuous interference of human beings as a bane post the rapid industrialization and urbanization. The ever increasing and decreasing ranges of temperature in the environment are leading to the malfunctioning of various physiological and biochemical processes in plants thereby resulting in severe temperature stresses in terms of high temperature/ he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Fahad et al (2016) reported the highest pollen fertility, anther dehiscence and pollen germination in rice cultivars with the application of brassinosteroids, methyl jasmonates along with Vitamin E and C and Sharma et al (2018) reported the mitigating effect of exogenous IAA application on spikelet fertility, pollen viability and yield components in 23 rice genotypes under high-temperature stress. Brassinosteroids (BR) are emerging as a new class of growth regulators which mitigate heat stress through enhancing the photosynthetic rate and antioxidative mechanism (Vidhyavardhini, 2019); enhancing chlorophyll content and reducing chlorophyllase activity regulating cell division and cell expansion; accumulating osmolytes; its interaction and cross-talk with other growth regulators in plants (Sharmaet al, 2017). Exogenous application of BR under heat stress at various concentrations haspositive impacts on several crops, including rice and wheat.…”
Section: Fig 3 Types Of Hsps Generated Under Stressed Conditions and ...mentioning
confidence: 99%
“…Fahad et al (2016) reported the highest pollen fertility, anther dehiscence and pollen germination in rice cultivars with the application of brassinosteroids, methyl jasmonates along with Vitamin E and C and Sharma et al (2018) reported the mitigating effect of exogenous IAA application on spikelet fertility, pollen viability and yield components in 23 rice genotypes under high-temperature stress. Brassinosteroids (BR) are emerging as a new class of growth regulators which mitigate heat stress through enhancing the photosynthetic rate and antioxidative mechanism (Vidhyavardhini, 2019); enhancing chlorophyll content and reducing chlorophyllase activity regulating cell division and cell expansion; accumulating osmolytes; its interaction and cross-talk with other growth regulators in plants (Sharmaet al, 2017). Exogenous application of BR under heat stress at various concentrations haspositive impacts on several crops, including rice and wheat.…”
Section: Fig 3 Types Of Hsps Generated Under Stressed Conditions and ...mentioning
confidence: 99%
“…BRs were initially extensively studied for their profound growth promoting physiological responses such as growth and yield, seed germination, photosynthesis, senescence, photomorphogenesis and flowering. BRs have been studied for its stress-protective characteristics in plants against a number of abiotic stresses [25].…”
Section: Brassinosteroids (Brs)mentioning
confidence: 99%
“…Moreover, GA is associated with SA/JA balance in the CBF-mediated stress response [24]. Brassinosteroids (BRs) have been explored for stress-protective properties in plants against a number of abiotic stresses [25]. BRs mitigated the damaging effect of chilling stress and increased the growth of cucumber seedlings [26].…”
Section: Introductionmentioning
confidence: 99%
“…Low temperatures at a range of 10 − 15°C cause chilling stress damage at any stage of eggplant growth and developmen (Abdel-Aziz and Geeth , 2019). The damage happend due to low temperature stress was alleviated by using some agricultural methods, like plant growth regulators (Orabi et al, 2015;Siddiqi, et al, 2019;Vardhini , 2019), planting in plastic house (Kwon et al, 2012) or through producing cold tolerance cultivars of eggplants (Singh et al, 2015). Eggplant cultivars differed in flowering, flower morphology and fruit setting (Sekara and Bieniasz, 2008), therefore, there is great variability of fruit setting and yielding among different varieties (Kowalska, 2008).…”
Section: Introductionmentioning
confidence: 99%